Reserve estimation method for Afsin-Elbistan Collolar brown-coal district - N. Celebi; K. Erarslan; A. G. Pasamehmetoglu (The Institute of Materials, Minerals and Mining, 1991)
A deposit evaluation system has been developed for a proposed new mine in the basin around Collolar in Turkey. It includes compositing, gridding and reserve estimation facilities and takes account of the economic value of the pit and the pit bottom elevation